Avoiding hetero/cissexist bias in psychological research: a contribution from latin America - Barrientos, Jaime; Radi, Blas (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2021)
This theoretical paper seeks to reflect on hetero/cissexist bias and how it could influence scientific papers and research on sexual diversity in the field of psychology. First, the paper defines and describes core concepts in this area, particularly, the notion of bias. Next, some of the most salient problems in this field are outlined, particularly the one concerning homo and transsexuality pathologization. Finally, some recommendations considered pertinent and useful for avoiding and minimizing bias are systematized.